Genetic Resources of Bamboos-an Indian Perspective - Mauria, S.; Arora, R. K. (Indian Forester, 1988)
This paper examines the distribution and diversity of different bamboos taxa in Indian context. The overall bamboo genetic resources scenario in the country is discussed to take stock of existing national resources to meet the increasing demand for exploitation of economically useful bamboo species and their conservation.